Effects of habitat and fishing on fish assemblages in a tropical reservoir: Lake Kariba, Zimbabwe. Issue 4 (December 2015) - Zengeya, Tsungai A.; Marshall, Brian E.
Abstract: This study investigated the effects of habitat and fishing on fish communities along inshore areas of the Sanyati Basin, Lake Kariba. A one‐year experimental gillnet survey was carried out in 2007 from eight sampling sites located in two different habitats (river mouths and sheltered bays), and in areas open or closed to fishing. A total of 16 species were captured, although the numbers caught at each site varied widely, with only four species recorded at each of the eight sampling sites. The numbers of fish were higher in the fished areas, mainly because of large numbers of Synodontis zambezensis, although the differences were not significant. In contrast, there were significant differences in the abundance of all species between habitats, with the exception of Cyphomyrus discorhynchus and Marcusenius macrolepidotus . There were no significant differences in the diversity of fish in these areas, although mean diversity and evenness were slightly higher in unfished areas and in sheltered bays. Overall, 90% of the fish specimens caught were within a 10–25 cm size range, although there were no systematic differences in the mean length in relation to fishing. In contrast, most fish were generally larger in river mouth areas than in sheltered bays. These data suggest that fishing had little effect on fish communities. This is in contrast to general habitat, which had a significant effect, a finding consistent with earlier studies showing that vegetation, in particular, had a significant effect on fish stocks.